A Retrospective Evaluation of the Steroid-Sparing Effect of Oral Modified Ciclosporin for Treatment of Canine Pemphigus Foliaceus - Eric Chong (Veterinary Sciences, 2022)
The efficacy of ciclosporin as an adjuvant immunosuppressant administered with glucocorticoids (GCs) for induction of canine PF remission is unknown. This study is a retrospective review of medical records from 2015 to 2020 to evaluate the therapeutic outcomes of 11 PF dogs treated with oral modified ciclosporin and GCs. Concurrent GCs were given with ciclosporin to all PF dogs. Nine dogs (9/11) achieved complete remission (CR); five dogs received ciclosporin at a mean dose of 6.2 mg/kg/day; and four dogs received a combination of ciclosporin and ketoconazole at a mean dose of 3 mg/kg/day, respectively. Two dogs (2/11) showed only 25% or poor response, with the development of new PF lesions during treatment. The mean duration of ciclosporin therapy for nine dogs to achieve CR was 65 days (median 57 days, range 24–119 days). Slow tapering of oral GCs while continuing ciclosporin at the same dose and frequency in nine dogs with CR led to recurrence of PF lesions in four dogs, whereas, in five dogs, oral glucocorticoids were discontinued without a PF flare. Oral modified ciclosporin combined with GCs achieved CR in 9 out of 11 PF dogs during the induction phase in this study.